2015
DOI: 10.1155/2015/959284
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric NO2Trends over South Asia during the Last Decade (2004–2014) Using OMI Data

Abstract: The focus of this study is to assess spatiotemporal variability of tropospheric NO2over South Asia using data from spaceborne OMI during the past decade (2004–2015). We find an average value of NO21.0 ± 0.05 × 1015 molec/cm2and a significant decadal increase of 14%. The elevating NO2pollution over the region is linked to rise in motor vehicles and industrial and agricultural activities and increase in biomass fuel usage. The observed seasonality of NO2is associated with change in meteorological conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…During the lockdown, the recorded tropospheric NO 2 concentration was 189.52 ×10 13 molecule cm −2 , whereas for the same period in 2019, the concentration was 225.64 ×10 13 molecule cm −2 . However, Ul-Haq et al. (2015) reported that in South Asia, including India, there was a significant decadal increase of 14% in NO 2 , and an estimated average tropospheric NO 2 concentration of 100.0 ± 0.05 × 10 13 molecule/cm 2 , over the region.…”
Section: Resultsmentioning
confidence: 99%
“…During the lockdown, the recorded tropospheric NO 2 concentration was 189.52 ×10 13 molecule cm −2 , whereas for the same period in 2019, the concentration was 225.64 ×10 13 molecule cm −2 . However, Ul-Haq et al. (2015) reported that in South Asia, including India, there was a significant decadal increase of 14% in NO 2 , and an estimated average tropospheric NO 2 concentration of 100.0 ± 0.05 × 10 13 molecule/cm 2 , over the region.…”
Section: Resultsmentioning
confidence: 99%
“…NO X and SO 2 pollution from power plants have increased by more than 70% from 1996 to 2014 and 2005-2012 respectively as observed by temporal trend observations from satellites Lu et al, 2013]. Trends in tropospheric NO 2 at selected industrial areas have been found to increase at a rate of 1 to 9% per year [Ramachandran et al, 2013], with a regional average decadal increase from 2004-2015 on the order of 14% [Zia ul-Haq et al, 2015]. The largest growth in VCDs is over areas of high population density in the north, attributable to enhanced electricity production, industrial activity, transportation, and crop burning, trends not as prominent in southern India [Duncan et al, 2015;Zia ul-Haq et al, 2015].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 82%
“…Trends in tropospheric NO 2 at selected industrial areas have been found to increase at a rate of 1 to 9% per year [Ramachandran et al, 2013], with a regional average decadal increase from 2004-2015 on the order of 14% [Zia ul-Haq et al, 2015]. The largest growth in VCDs is over areas of high population density in the north, attributable to enhanced electricity production, industrial activity, transportation, and crop burning, trends not as prominent in southern India [Duncan et al, 2015;Zia ul-Haq et al, 2015]. However, recent developments, including slight stagnation due to economic slow-down [Hilboll et al, 2017], indicate the complex nature of pollution trends in the region which may be unaccounted for in current emissions inventories for the region.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…OMI AURA satellite observation of NO 2 concentrations [ 19 , 24 ] over India shows high concentrations at few locations, one of the locations correspond to the location of the seven coal-fired power plants (Singrauli). The NO 2 and AOD show higher correlation based on satellite data [ 19 , 20 , 21 , 25 ]. The higher tropospheric NO 2 concentrations over the Singrauli area, seen from the OMI AURA satellite ( Figure 1 ) is considered for the in-situ BC and aerosol measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The black carbon concentration absorbs Sun radiations and impacts global climate as well as regional climate and monsoon [ 6 , 17 ]. Coal-fired power plants are densely located in the Indo-Gangetic Plain (IGP) and are considered as one of the sources of atmospheric pollution in the IGP [ 18 , 19 , 20 , 21 , 22 , 23 ]. The coal-fired thermal power plants are one of the major energy sources in India, the density of these power plants are very high in the northern and south-east parts of India, especially in the IGP.…”
Section: Introductionmentioning
confidence: 99%